Existence and dialectical ambiguity: the presence of Hegel in the thought of Simone de Beauvoir - Teixeira, Nathan Menezes Amarante (Sofia, 2025)
This article seeks to clarify the extent to which Hegelian dialectics is a decisive basis for the way Simone de Beauvoir understands existence and characterizes it as ambiguous. As will be discussed, it is from the dialectical development of self-consciousness presented by Hegel, in which the moment “being for the other” is shown as the necessary mediation for the constitution of being for oneself, that Beauvoir will build her understanding of bodily presence. In this sense, Simone de Beauvoir will assume the continuous dialectical fragmentation of becoming oneself as always having to return to oneself from being for the other, at the same time that she will propose that this relation be conceived as a commitment of the body to its own objectivity outside itself, in such a way that it presents a change in the specific Hegelian way of thinking about this relation but from the general acceptance of its premises, a moment in which the idea of ambiguity as a relationship of inherence and detachment will be developed.
Keywords: Simone de Beauvoir; Hegel; dialectics; ambiguity; existence